Parent-Reported Suicidal Ideation in Three Population-Based Samples of School-Aged Korean Children With Autism Spectrum Disorder and Autism Spectrum Screening Questionnaire Screen Positivity. Issue 3 (3rd July 2022) - Bal, Vanessa H.; Leventhal, Bennett L.; Carter, Gregory; Kim, Hosanna; Koh, Yun-Joo; Ha, Mina; Kwon, Ho-Jang; Hong, Patricia; Kim, Young Shin
Abstract: Objectives: Higher prevalence of suicidality has been reported in individuals with ASD. This study aimed to (1) Estimate the prevalence of suicidal ideation (SI) in epidemiologically-ascertained, population-based, samples of children with ASD or Autism Spectrum Screening Questionnaire (ASSQ) Screen Positivity (ASP); (2) Determine whether ASD/ASP is an independent risk factor for SI, controlling for known SI risk factors; and, (3) Develop an explanatory model for SI in children with ASD/ASP. Methods: Participants came from three epidemiologically-ascertained samples of school-aged Korean children ( n = 14, 423; 3, 702; 4, 837). ASSQ ≥ 14 was the cutoff for ASP. A subsample ( n = 86) was confirmed to have ASD. SI was based on parents' endorsement of items on the Behavioral Assessment System for Children-2-Parent Report Scale-Children. Logistic regressions were used to assess associations between SI and ASD/ASP, controlling for demographics, peer victimization, behavior problems, and depression. To develop an explanatory model for SI within ASD/ASP, the associations between SI and child characteristics (comorbid conditions, ASD symptoms, IQ, adaptive function) were tested. Results: SI was higher in children with ASD (14%) and ASP (16.6–27.4%) than ASSQ Screen Negative (ASN) peers (3.4–6.9%). ASD/ASP was strongly predictive of SI (ORs: 2.87–5.67), after controlling for known SI risk factors compared to ASN. Within the ASD and ASP groups, anxiety was the strongest predictor of SI. Conclusions: SI prevalence was higher in non-clinical samples of children with ASD and ASP, relative to ASN peers. These results underscore the need for routine screening for SI in children with ASD and social difficulties, particularly those with high anxiety. Highlights: Population-based, epidemiologically-ascertained, school-aged children ASD and ASP are independent risk factors for SI in school-aged children Anxiety is an independent risk factor for SI in children with ASD or ASP